Combination of AZD3463 and DZNep Prevents Bone Metastasis of Breast Cancer by Suppressing Akt Signaling - He, Wenxin; Cao, Xiankun; Rong, Kewei; Chen, Xiaojun; Han, Shuai; Qin, An (Frontiers in Pharmacology, 2021)
Osteolysis resulting from osteoclast overactivation is one of the severe complications of breast cancer metastasis to the bone. Previous studies reported that the anti-cancer agent DZNep induces cancer cell apoptosis by activating Akt signaling. However, the effect of DZNep on breast cancer bone metastasis is unknown. We previously found that DZNep enhances osteoclast differentiation by activating Akt. Therefore, we explored the use of the anti-cancer agent AZD3463 (an Akt inhibitor) along with DZNep, as AZD3463 can act as an anti-cancer agent and can also potentially ameliorate bone erosion. We evaluated osteoclast and breast cancer cell phenotypes and Akt signaling in vitro by treating cells with DZNep and AZD3463. Furthermore, we developed a breast cancer bone metastasis animal model in mouse tibiae to further determine their combined effects in vivo. Treatment of osteoclast precursor cells with DZNep alone increased osteoclast differentiation, bone resorption, and expression of osteoclast-specific genes. These effects were ameliorated by AZD3463. The combination of DZNep and AZD3463 inhibited breast cancer cell proliferation, colony formation, migration, and invasion. Finally, intraperitoneal injection of DZNep and AZD3463 ameliorated tumor progression and protected against bone loss. In summary, DZNep combined with AZD3463 prevented skeletal complications and inhibited breast cancer progression by suppressing Akt signaling.